2019
DOI: 10.56093/ijans.v89i5.90033
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of silver pompano Trachinotus blochii (Lacepede, 1801) at different salinities in inland saline ground water

Abstract: Inland saline ground water (ISGW) has attracted great interest for commercial aquaculture of marine species in Haryana and Punjab. The silver pompano (Trachinotus blochii), a candidate for mariculture, was investigated for its potential to survive in inland saline water at ICAR-CIFE, Regional Centre, Rohtak, Haryana during 2015–16. The experimental set up comprised ISGW without potassium amendment, ISGW with potassium amendment and artificial sea water of 5 ppt, 10 ppt and 15 ppt salinity. In ISGW without po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Ionic regulation has strong relation with iso-osmotic point, wherein fish does not have to spend more energy to maintain homeostasis. Therefore, Pathak et al (2019) suggested that fish regulated osmotic balance at ISW10 and ISW15 as the iso-osmotic point of T. blochii was in between 10-15 ppt, which was reconfirmed in the present study with higher serum K + concentration at ISW10 and ISW15. Also, previous study reported higher uptake of potassium at near-isosmotic salinities in Argyrosomus japonicas reared in saline ground water supplemented with 100% K + of similar salinities (Partridge and Lymbery, 2008;2009).…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…Ionic regulation has strong relation with iso-osmotic point, wherein fish does not have to spend more energy to maintain homeostasis. Therefore, Pathak et al (2019) suggested that fish regulated osmotic balance at ISW10 and ISW15 as the iso-osmotic point of T. blochii was in between 10-15 ppt, which was reconfirmed in the present study with higher serum K + concentration at ISW10 and ISW15. Also, previous study reported higher uptake of potassium at near-isosmotic salinities in Argyrosomus japonicas reared in saline ground water supplemented with 100% K + of similar salinities (Partridge and Lymbery, 2008;2009).…”
Section: Resultssupporting
confidence: 84%
“…Thus, in order to ascertain the feasibility of rearing T. blochii in ISW, a study was conducted to determine physiological responses. Growth performance of T. blochii juveniles in terms of mean final body weight, weight gain, specific growth rate and average daily growth was significantly higher at 10 and 15 ppt ISW compared to 5 ppt (Pathak et al, 2019).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations